Interpersonal neural synchronization underlies mnemonic similarity during collaborative remembering - Zhang, Huan; Wang, Haiman; Long, Yuhang; Jiang, Yunpeng; Lu, Chunming (Neuropsychologia, 2023)
Although collaborative remembering is a ubiquitous feature of human beings, its underlying neurocognitive process is not well understood. Here we hypothesized that interpersonal neural synchronization (INS) might underlie collaborative remembering, while real collaboration as opposed to other modes of offline collaboration should enhance INS and facilitate mnemonic similarity. To test these hypotheses, brain activity was measured simultaneously from two individuals who performed a group-based selective retrieval practice task either in a real collaboration or in a pseudo-collaboration, i.e., an individual performed the task together with a pre-recorded audio. The results showed that the memory of two individuals converged to a greater level than the chance level in real collaboration but not in control condition. Moreover, collaborative remembering was associated with significant INS increase in the prefrontal cortex (PFC) relative to the baseline in the real collaboration only. Additionally, INS increase was significantly greater in the real collaboration than in control condition. Finally, the PFC's INS increase was positively correlated with and could accurately predict the level of mnemonic similarity in real collaboration. These findings support the hypothesis that the enhanced INS underlies the cognitive process of collaborative remembering.